Comparative Analysis of Stock and Mutual Fund Allocation Among Generation Z Based on Behavioral Finance Factors (A Study of Generation Z in Surabaya) - Reza Syahputra Sijabat; Nurhadi Nurhadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
The rapid surge of Generation Z participation in the Indonesian capital market has created a new investor landscape, yet this growth is often not aligned with adequate financial literacy, leading to potential irrationality in asset selection. This research aims to analyze and compare the allocation of stock and mutual fund portfolios among Generation Z investors, specifically examining the influence of financial literacy and various behavioral factors, including return expectations, risk tolerance, and herding tendencies. Using a quantitative comparative methodology, the study focused on the Inflow Community in Surabaya as a representative demographic. Data were gathered from 110 respondents through purposive sampling and analyzed using the Kruskal-Wallis non-parametric test, necessitated by the non-normal distribution of the dataset. The study concludes that there is a statistically significant difference in portfolio allocation between stocks and mutual funds, as evidenced by an asymptotic significance value of < 0.001. These differences are primarily driven by varying degrees of financial literacy and the prevalence of herding behavior among young investors. Based on these findings, it is recommended that financial regulators and educational institutions design more personalized financial literacy programs. Such programs should not only cover technical analysis but also address the psychological aspects of investing, such as emotional control and independent decision-making, to assist Generation Z in achieving more optimal and rational long-term wealth management.